THE RELATIONSHIP BETWEEN NITRATE AND PHOSPHATE CONTENT AND DIATOM ABUNDANCE IN THE WATERS OF PANDAN ISLAND, WEST SUMATRA - Moulidia, Candri; Nedi, Syahril; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This research was conducted in the waters of Pandan Island, West Sumatra, to determine the content of nitrates, phosphates, and diatom abundance and the relationship between nitrate and phosphate concentrations and diatom abundance. The method used is the survey method. The sampling station is determined by purposive sampling based on cardinality. Define the relationship between nitrate and phosphate content content and diatom abundance using simple linear regression. The results showed that there were eight species of diatoms with the class Bacillariophyceae, including Isthmia sp, Amphora sp, Closterium sp, Nitzschia sp, Hemiaulus sp, Asterionella formosa, Leptocylindrus sp. The highest diatom abundance was at station IV, with an average abundance value of 14.092,09 ind/L, and the lowest abundance was at station I, with an average of 5.317,77 ind/L. The relationship between nitrate concentration and diatom productivity was obtained with the value of y = 31.184x-15.082 and the correlation coefficient (r) = 0.711. Meanwhile, the phosphate concentration on diatom productivity was obtained with a value of y = 51.543x-32.477 and a relational (r) coefficient value = 0.738. There is a strong relationship between nitrate and phosphate content and diatom abundance in the waters of Pandan Island, West Sumatra